2008
DOI: 10.1144/sp308.21
|View full text |Cite
|
Sign up to set email alerts
|

Empirical thermometer of TiO 2 in quartz for ultrahigh-temperature granulites of East Antarctica

Abstract: Two preliminary experiments, heating of rutilated quartz grains with 0.082 wt% TiO2 on average from Bunt Island, Napier Complex, East Antarctica and a synthetic TiO2–SiO2 (rutile–cristobalite) system in air at 1300 °C for 39 days, showed increasing solubility of TiO2 in silica minerals with temperature. Bunt quartz was converted to cristobalite and traversed by many transparent seams with the disappearen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…Temperatures calculated by the geothermometers of Thomas et al (2010) and Kawasaki & Osanai (2008) are anomalously low relative to those predicted by thermal modelling [Buntebarth, 1991] …”
Section: 3) La-icp-msmentioning
confidence: 66%
See 2 more Smart Citations
“…Temperatures calculated by the geothermometers of Thomas et al (2010) and Kawasaki & Osanai (2008) are anomalously low relative to those predicted by thermal modelling [Buntebarth, 1991] …”
Section: 3) La-icp-msmentioning
confidence: 66%
“…The original TitaniQ geothermometer was later refined to include a pressure coefficient by Thomas et al [2010], supposedly allowing temperature determinations from known pressure, and vice versa (Equation 3). A granulite-derived Ti-in-Quartz geothermometer was later developed by Kawasaki and Osanai, [2008] using natural rocks from Antarctica (Equation 4). This, and the geothermometer of Thomas et al [2010] Recently, Wilson et al, [in press] has cast doubt on the validity of any Ti-in-Quartz geothermometry due to the poorly constrained speciation of Ti in any fluids involved.…”
Section: T(°c)mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies supporting both calibrations exist (Leeman et al, 2012;Wilson et al, 2012;Ashley et al, 2013;Aude¤ tat, 2013;Morgan et al, 2013;Kularatne & Aude¤ tat, 2014), suggesting that the two calibrations might be appropriate in different geological settings or that their success might be dependent on aTiO 2 (Leeman et al, 2012; Thomas & Watson, 2012;Wilson et al, 2012;Morgan et al, 2013;Kularatne & Aude¤ tat, 2014). It should be noted that an alternative TitaniQ calibration by Kawasaki & Osanai (2008), as well as the calibration by Wark & Watson (2006), does not include a pressure dependence and will not be included in the following discussion.…”
Section: T H E R M O M E T Ry Ti-in-quartz Thermometermentioning
confidence: 97%
“…The Ti content in olivine was found to increase with pressure (Dobrzhinetskaya et al, 2000) whereas Hermann et al (2005) demonstrated that it decreases with pressure. The Ti-in-quartz thermometer has been experimentally (Wark and Watson, 2006;Ostapenko et al, 2007;Thomas et al, 2010;Huang and Audétat, 2012) and empirically (Kawasaki and Osanai, 2008) calibrated for the temperature estimation of ultrahigh-temperature granulites. and Dwarzski et al (2006) reported that the TiO 2 solubility increases with pressure in majoritic garnet.…”
Section: Introductionmentioning
confidence: 99%